(untitled) (Ameghiniana, 2020)
The present work introduces the first anatomical and systematic study of a fossil wood found in the Northern Pampa. The diagnostic anatomical features of the fossil wood are common in the Proteaceae family and Roupala genus. This fossil wood can be included within the organ genus Scalarixylon, Pujana. This family is considered a relict group from Gondwana because of its disjunct modern distribution in Australia, Africa, Central and South America, and limited places in Asia and the Pacific Isla. This finding is particularly significant for future paleobiogeography interpretations about this region and for the occurrence of Proteaceae fossil in the Paraná Basin over the Pleistocene.